Business Plan : Bakers Passion Bakery / Nur Maisarah Zamani…[et al.] - Zamani, Nur Maisarah; Mohd Mohamadiah, Nabila Hanim; Torji, Fatin Amirah; Mohd Yusoff, Nur Aisha; Johari, Nurhana ‘Alyaa; Ismawadi, Siti Aishah (2021)
First and foremost, for the third assessment for the subject of Fundamental of Entrepreneurship (ENT300) which is business plan, students are required to form a group consisting of several members and need to create a business partnership. Therefore, my group of 6 members, namely Maisarah, Fatin, Nabila, Aisha, Hana, and also Aishah agreed to create a bakery named "Bakers Passion Bakery". Generally, this bakery is just a small shop that sells and accepts orders for cakes, breads, muffins, macaroon and many other desserts. We also provide various types of coffee such as cappuccino, latte, Arabica and so on to customers as there are many coffee lovers in Malaysia. This bakery has a concept of elegant style but quite relaxed so that customers are comfortable and calm when entering this shop. The location of the "Bakers Passion Bakery" bakery can be said to be quite strategic as it is located in a relatively developed area and is inhabited by many residents from various walks of life. Although there are also other bakeries established here, our bakery has a different environment and taste, where the ingredients we use in the production of these desserts are healthy and high-quality ingredients. This is because we are very concerned on the customer satisfaction in every single bite of the desserts prepared by us. In the meantime, the idea for the opening of this bakery began to emerge because each of us has our own expertise in making desserts. With this, we can ensure that the expertise we have is not wasted and that the cooperation between us can produce such a special taste of dessert that may be beyond people's expectations.